Association of Temporomandibular Disorder Symptoms with Physical Fitness among Finnish Conscripts - Miettinen, Ossi (Int J Environ Res Public Health, 2021)
Studies on the role of physical fitness, physical activity and obesity as risk factors for temporomandibular disorders (TMD) are scarce. The aim of the present study was to evaluate the association of TMD symptoms with physical fitness, physical activity and body mass index (BMI) among Finnish conscripts. The study sample consisted of 8685 Finnish conscripts. Data on self-reported TMD symptoms were used as outcome variables. Physical activity (questionnaire), physical fitness (measured with physical tests: Cooper test, push-ups, sit-ups and standing long jump) and body mass index (BMI) were used as explanatory variables. The associations between TMD symptoms and explanatory variables were evaluated using Chi-squared test and logistic regression analysis. The prevalence of all TMD symptoms was significantly higher among those who exercised more rarely than weekly. Pain-related TMD symptoms were also significantly more frequent among those who were overweight (BMI ≥ 25). Poor push-up results and overweight (BMI ≥ 25) were significantly associated with jaw pain and TMJ pain at jaw rest. The present study showed that good physical fitness may be a protective factor against TMD pain. Dentists should also be prepared to motivate TMD patients to physical activity and regular exercise as part of the treatment.